A brief atlas of the human body - Hutchinson, M.; Mallatt, J.; Marieb, E. M.; Wilhelm, P. B. (Pearson Education, 2007)
Atlas mit 21 beschrifteten Weichteil- und 105 Knochen-Bildern des menschlichen Körpers.